2013
DOI: 10.2350/12-06-1216-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Glypican-3 in Pediatric Tumors: An Analysis of 414 Cases

Abstract: Glypican-3 (GPC3) is a proteoglycan thought to play an important role during development. Germline GPC3 mutations are seen in the rare Simpson-Golabi-Behmel syndrome (SGBS), which predisposes patients to Wilms tumor, hepatoblastoma, and neuroblastoma. While numerous adult tumors have been evaluated by immunohistochemistry for GPC3, no comprehensive assessment has been done in pediatric tumors. We therefore investigated GPC3 expression in 143 pediatric central nervous system (CNS) tumors and 271 non-CNS tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
2
29
0
2
Order By: Relevance
“…reported that six (43%) of 14 MRTs showed a significant extent of glypican 3 expression, whereas it was observed in only one (2%) of 48 ESs. A high prevalence of glypican 3 immunoexpression in MRTs has also been reported by other groups . Glypican 3 and SALL4 are sometimes coexpressed in tumour tissues.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…reported that six (43%) of 14 MRTs showed a significant extent of glypican 3 expression, whereas it was observed in only one (2%) of 48 ESs. A high prevalence of glypican 3 immunoexpression in MRTs has also been reported by other groups . Glypican 3 and SALL4 are sometimes coexpressed in tumour tissues.…”
Section: Discussionsupporting
confidence: 75%
“…A high prevalence of glypican 3 immunoexpression in MRTs has also been reported by other groups. 18,34 Glypican 3 and SALL4 are sometimes coexpressed in tumour tissues. For example, both are known to be sensitive markers for yolk sac tumour, 20,22 and the expression of glypican 3 and that of SALL4 are significantly interrelated in gastric adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of GPC-3 was found in the following cancers: liver, gastric carcinoma, melanoma, highgrade urothelial carcinoma, testicular, and some uterine and vaginal cancers (1,3-6,23,28,33-35). GPC-3 expression was also reported in some non-CNS tumors of the brain (36). In various other tissue types such as colon, lung, anal, esophageal, mouth mucosa, pancreas, skin, thyroid, bladder, uterus, and vulvar tissue GPC-3 expression varied based on the type, and origin, and grade of cancer [i.e.…”
Section: Expression Of Gpc-3 In Cancer Tissue Gpc-3 Expression Inmentioning
confidence: 95%
“…It was a predictable result that most of our NB cases (n=35) showed no GPC3 immunoreactivity, and also showed low GPC3 mRNA expression levels. Chan et al reported that the immunohistochemical GPC3 expression was entirely negative in clinical samples of NB (21), whereas Saikali and Sinnett reported increased GPC3 mRNA expression levels in most of the 10 NB cell lines they examined (11). Further studies using a larger number of NB cases are required to confirm the correlation between GPC3 immunoreactivity and the mRNA expression level.…”
Section: Discussionmentioning
confidence: 97%